Current developments in prevention and treatment of candidiasis: A review - Chakraborty, Prodipta; Pradhan, Darshan; Halder, Sudip; Bagchi, Arnab (Creative Pharma Assent, 2021)
Invasive fungus infection affects about six people out of every 100,000 people each year. Only half of these infections are detected throughout the patient's lifetime, making it one of the most common causes of death among intensive-care patients. The low detection rate is due to the diagnostic work's complexity, which comprises clinical, radiographic, and microbiological results. Antimycotic drug-resistant fungi are on the rise all over the world. Guidelines for identifying and treating invasive fungous infections caused by Candida spp., Aspergillus spp., Mucorales, and Fusarium spp. are the topic of this review. In typical hospital care, intrusive fungous infections are frequently ignored. They must include it as a necessary component of antimicrobial stewardship programmes. There is also a great need for novel antimycotic medication classes to be developed